MY SAY: Healing the divisiveness of Sept 11 - Abd Razak, Dzulkifli (2010)
Anything to do with the 9/11 incident has been divisive from the start, be it religion, politics or even development issues on what is now known as ground zero. The decision to build the Freedom Tower — the main building of the new World Trade Center complex in lower Manhattan in New York City — was criticised at one point because it was "too tall and too attractive to terrorists to attract corporate tenants". Others called it a "speculative white elephant".